Nucleotidic variations of two captive groups of tepezcuintle, Agouti paca (Rodentia: Agoutidae), from two sites in Yucatan, Mexico - Montes Pérez, Rubén C. (2006)
The objective of this work was to estimate the nucleotidic variation between two groups of tepezcuintles (Agouti paca) from the states of Campeche and Quintana Roo, Mexico and within members of each group. Blood samples were collected from eleven A. paca kept in captivity. DNA from leukocytic cells was used for Ramdom Amplification of DNA Polimorphism (RAPD). The primers three 5'-d(GTAGACCCGT)- 3' and six 5'-d(CCCGTCAGCA)- 3' were selected from de Amersham kit (Ready.To.Go. RAPD Analysis Beads, Amersham Pharmacia Biotech), because they produced an adequate number of bands. The electrophoretic pattern of bands obtained was analyzed using software for phylogenetic analysis based on the UPGMA method, to estimate the units of nucleotidic variation. The phylogenetic tree obtained with primer three reveals a dicotomic grouping between the animals from both states in the Yucatan Peninsula showing a divergent value of 1.983 nucleotides per hundred. Animals from Quintana Roo show a grouping with primer six; an additional grouping was observed with animals from Campeche. Nucleotidic variation between both groups was 2.118 nucleotides per hundred. The nucleotidic variation for the two primers within the groups from both states, showed fluctuating values from 0.46 to 1.68 nucleotides per hundred, which indicates that nucleotidic variation between the two groups of animals is around two nucleotides per hundred and, within the groups, less than 1.7 nucleotides per hundred.